Pemanfaatan Media Sosial Berbasis AR Untuk Mengidentifikasi Dalam Pemilihan Bingkai Kacamata Pada Toko Kacamata Idri - Valensia, Vally; Kurniabudi, Kurniabudi (LPPM Universitas Dinamika Bangsa, 2023)
At the Toko Kacamata Idri, currently users who want to buy glasses can try the product directly and use it physically at the shop or glasses users who are far outside the city can order via Instagram or Whatsapp. However, ordering online makes glasses users unable to see and try the shape of the glasses ordered directly due to the distance constraint. This study aims to develop virtual eyeglass frames based on Augmented Reality with the Face Tracker Decoration method and the Augmented Reality Random method which are able to provide views and recommendations for glasses based on face shape by adapting the morphology of facial indexes as determining the type of face at the Toko Kacamata Idri. This design is done using the Meta Spark Studio application. The design results are in the form of effects that can be used in the Instagram application. There are three designs in this study, effect designs to identify face types, effects designs to display glasses recommendations and designs to display eyewear products.